2006
DOI: 10.1309/v1ry91nkx5arw2q5
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen, High-Molecular-Weight Cytokeratin (Clone 34βE12), and/or p63

Abstract: An optimal immunohistochemical panel to distinguish poorly differentiated prostate (PCa) from urothelial (UCa) carcinoma was selected from a panel consisting of prostate-specific antigen (PSA) and prostatic acid phosphatase (PAP), high-molecular-weight cytokeratin (HMWCK), clone 34betaE12, cytokeratin (CK) 7, CK20, p63, and alpha-methylacyl-coenzyme A racemase. The pilot group was composed of poorly differentiated UCa (n = 36) and PCa (n = 42). PSA and PAP stained 95% of PCa vs 0% and 11% of UCa cases, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Of the 13 UC cases that were negative for p63, 3 cases had micropapillary features. Our results are comparable to Kunju et al [15] who also found diffuse nuclear p63 positivity in 92% of their UC cases using the same p63 monoclonal antibody. Chuang et al [3] using the same p63 antibody found p63 in 83% of their UC cases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 13 UC cases that were negative for p63, 3 cases had micropapillary features. Our results are comparable to Kunju et al [15] who also found diffuse nuclear p63 positivity in 92% of their UC cases using the same p63 monoclonal antibody. Chuang et al [3] using the same p63 antibody found p63 in 83% of their UC cases.…”
Section: Discussionsupporting
confidence: 90%
“…Although the diagnostic utility of p63 and P501S in distinguishing between primary PC and UC have been individually evaluated previously [3,11,15], thus far, there have been no previous studies evaluating these two markers together either as a cocktail or applied sequentially. Our results indicate that dual-color immunohistochemistry with p63 and P501S applied sequentially shows excellent specificity for distinguishing UC from PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most suitable methods for differentiation is the use of immunohistochemistry (IHC) because many immunohistochemistry markers are different in these two tumors (9,10). Prostate-specific antigen (PSA) is an appropriate marker for PCa, and Cytokeratin 7 (CK7) and high-molecular-weight cytokeratin (HMWK) clone 34β£12 are suitable markers for bladder carcinoma (11), and their combination can play a significant role in differentiating these cancers (12,13). Two prostatic Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Rectum adenocarcinoma, urothelial carcinoma, or bladder adenocarcinoma cannot produce PSA (22). The 34β£12 or HMWK antibody is a nonsensitive but highly specific marker for differentiating the transitional bladder carcinoma from prostate adenocarcinoma (11,23). The 34β£12 antibody specifically detects the basal cells.…”
Section: Introductionmentioning
confidence: 99%